Perkembangan Konseptual dan Eksistensi Konvensi Ketatanegaraan Pasca-Perubahan Konstitusi - Mei Susanto (Undang: Jurnal Hukum, 2021)
The existence of constitutional conventions in Indonesia after the Amendment of the 1945 Constitution is problematic due to the abolition of the Explanation of the Constitution. Through a conceptual approach, this article answers its problem that constitutional conventions still exist because conventions are sub-systems that are always attached and present in the state constitutional system everywhere, including Indonesia. This article further discusses the development of constitutional conventions starting from the doctrine presented by Dicey in 1885 to current opinions by classifying the development of the term, source/rise, function, binding and obedience, mode of change, and the role of the court. From these developments, the understanding of constitutional conventions in Indonesia cannot be based on old doctrines or examples that tend to be out of date because conventions adapt like 'amoeba', not only in the context of carrying out the constitutional process but also filling in the gaps to complete the constitutional law supposed to be filled in by written law. Therefore, there are two important urgencies: first, academic urgency in the form of enrichment and deepening of conventions through teaching and research; second, the urgency of the constitutional practice of the Indonesian constitutional system, especially conventions that strengthen the principle of the constitution, democracy, and political accountability, both in executive institutions, the legislature, including the courts. The constitutional practice is not enough just to look at the written constitutional law, but also the principles, ethics, and morality accompanying the Indonesian constitutional system. Abstrak Eksistensi konvensi ketatanegaraan di Indonesia Pasca-Perubahan Konstitusi UUD 1945 kerap dipersoalkan sebagai dampak dihapuskannya bagian Penjelasan. Melalui pendekatan konseptual, artikel ini menjawab persoalan tersebut bahwa konvensi ketatanegaraan tetaplah eksis karena konvensi merupakan sub-sistem yang selalu melekat dan hadir pada sistem ketatanegaraan negara di mana-pun termasuk Indonesia. Artikel ini lebih jauh membahas perkembangan konvensi ketatanegaraan mulai dari doktrin yang disampaikan Dicey pada 1885 sampai dengan pendapat-pendapat kontemporer, dengan mengelompokkan pada perkembangan istilah, awal mula terbentuk, fungsi, daya ikat dan kepatuhan, cara perubahan, serta peranan pengadilan. Dari perkembangan tersebut, maka pemahaman terhadap konvensi ketatanegaraan di Indonesia tidak dapat disandarkan pada doktrin maupun contoh-contoh lama yang cenderung out of date, karena konvensi beradaptasi layaknya ‘amoeba’, tidak hanya dalam rangka menjalankan proses ketatanegaraan, namun juga mengisi kekosongan guna menyempurnakan hukum ketatanegaraan yang seharusnya diisi oleh hukum tertulis. Karena itu, terdapat dua urgensi penting: pertama urgensi akademik berupa pengayaan dan pendalaman konvensi melalui pengajaran dan penelitian; kedua, urgensi praktik penyelenggaraan ketatanegaraan Indonesia khususnya konvensi yang memperkuat sendi konstitusi, demokrasi dan akuntabilitas politik, baik pada lembaga ekskekutif, legislatif, termasuk pengadilan. Penyelenggaraan negara sejatinya tidak cukup hanya dengan melihat hukum ketatanegaraan tertulis semata, melainkan dibutuhkan juga prinsip, etika dan moralitas yang membersamai ketatanegaraan Indonesia.